Active Mobility and Subjective General Health: Roles of Mental Health, Social Support and Physical Activity. (June 2017) - Avila-Palencia, Ione; Panis, Luc Int; de Nazelle, Audrey; Götschi, Thomas; Raser, Elisabeth; Gaupp-Berghausen, Mailin; Stigell, Erik; Iacorossi, Francesco; Laeremans, Michelle; Boig, Esther Anaya; Nieuwenhuijsen, Mark
Abstract : Background: Active mobility (i.e. walking and cycling) has been associated with multiple health benefits from reduction to cardiovascular risk, lowering of body weight, improvement of fitness, reduced risk of diabetes, to higher levels of physical and mental well-being. The association between active mobility and subjective general health remains unexplored, as are the mechanisms which mediate this association. The current study evaluates the association between active mobility and subjective general health in an adult population in seven European cities, and explores whether mental health, vitality, stress, social support, and physical activity are mediators of this association. Methods: A cross-sectional study has been performed in seven European cities (Antwerp, Barcelona, London, Örebro, Rome, Vienna, and Zürich). Participants responded to a comprehensive survey concerning their mobility behaviour and self-perceived health. Participants were categorized as either those who have active mobility patterns or non-active mobility patterns, and as with "good or more" or "less than good" subjective general health. Multilevel Logistic regression models will be used to evaluate the association between subjective general health status and active mobility, adjusting for potential confounders. We will follow Baron and Kenny's framework to establish the mediation roles and we will further quantify the relative contribution of each mediator. Results: Analyses are on-going. The sample had more than 3, 000 adults, fairly distributed in the seven cities (16% Antwerp, 16% Barcelona, 14% London, 10% Örebro, 14% Rome, 16% Vienna, 14% Zürich). We expect to find association between active mobility use and better subjective general health. We also expect to find indications for mediation of this association by mental health status, perceived social support, perceived stress, and physical activity. Conclusions: A better mental health status, perceived social support, perceived stress and higher levels of physical activity may be important consequences of active mobility which could lead to a better subjective general health. these should be considered by decision makers as other potential benefits of active mobility promotion.